The influence of Internet and social media on purchasing decisions in Indonesia and a comparison between Indonesia and Kuwait - al-enizi, Khalid; Taha Alshaikhli, Imad Fakhri; Mahmood Aldabbagh, Sufyan Salim; Mohammad Alwuhaib, Jassim (American Scientific Publishers, 2019)
This research aims to understand the role of the Internet and in particular, the social media in affecting purchasing behavior among the social media users in Indonesia; furthermore, discuss results from the current research, and other papers conducted in the same field for Kuwait. The researcher used the quantitative methods, and analytical techniques to obtain the required outcome. The researcher developed a measure to acquiring the way that the variables are connected in this study. Primary data of Indonesia were collected from major surveys and digital analytics, Audience Insight Tools and Trends performed by GlobalWebIndex, Yanuar Nugroho, and ComScore Mobile Internet. The independent and dependent variable; first, the independent v ariable was social networks (The Product Rating, Consumer support exchange of information), and second the dependent variable was a consumer willing to buy products. The results in Indonesia mostly stems from some elements such as conventional advertising (TV, Magazine, Newspaper, Outdoors) it is considered more effective than the social media, and close to Kuwait’s results. Indonesian is one of the world most extensive use of the social media with an average of 80% of the total online activities. Fashion and travel/accommodation are the most extensive shopping areas of Indonesian, Kuwaitis are interested in Fashion, decoration, and cultural. Due to the lifestyle, Kuwaitis are using the social media extensively for commercial propose more than Indonesian. As results of this paper, the researcher introduced a series of recommendations based on t hat; the consumer sometimes does not find the appropriate information to make the purchase decision